A geometrical constant and normal normal structure in Banach Spaces - Zuo Zhanfei (Journal of Inequalities and Applications, 2011)
Abstract Recently, we introduced a new coefficient as a generalization of the modulus of smoothness and Pythagorean modulus such as JX , p (t). In this paper, We can compute the constant JX , p (1) under the absolute normalized norms on ℝ2 by means of their corresponding continuous convex functions on [0, 1]. Moreover, some sufficient conditions which imply uniform normal structure are presented. 2000 Mathematics Subject Classification: 46B20.